2010
DOI: 10.1093/bioinformatics/btq447
|View full text |Cite
|
Sign up to set email alerts
|

DMDM: domain mapping of disease mutations

Abstract: Freely available at http://bioinf.umbc.edu/dmdm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 18 publications
1
48
0
Order By: Relevance
“…The resulting PCR products were then subjected to direct sequencing using the same primers, and all variants were confirmed by sequences originating from both upstream and downstream primers. Of the patients analyzed, 210 exhibited nonsynonymous sequence variants in the sequenced exons that were checked in COSMIC (Forbes et al, 2011), Humsavar (Humsavar Database, Geneva, Switzerland: Swiss Institute of Bioinformatics, http://www.uniprot.org/docs/humsavar), ClinVar (ClinVar database, Release weekly,Bethesda, MD, USA: National Center for Biotechnology Information, US, National Library of Medicine, (http://www.ncbi.nlm.nih.gov/clinvar/), DMDM (Peterson et al, 2010) and bibliographic databases to verify previous reports. To evaluate whether these variants involved structural and/or functionally relevant positions, the structures of different conformers were extracted from the CoDNas database (Monzon et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting PCR products were then subjected to direct sequencing using the same primers, and all variants were confirmed by sequences originating from both upstream and downstream primers. Of the patients analyzed, 210 exhibited nonsynonymous sequence variants in the sequenced exons that were checked in COSMIC (Forbes et al, 2011), Humsavar (Humsavar Database, Geneva, Switzerland: Swiss Institute of Bioinformatics, http://www.uniprot.org/docs/humsavar), ClinVar (ClinVar database, Release weekly,Bethesda, MD, USA: National Center for Biotechnology Information, US, National Library of Medicine, (http://www.ncbi.nlm.nih.gov/clinvar/), DMDM (Peterson et al, 2010) and bibliographic databases to verify previous reports. To evaluate whether these variants involved structural and/or functionally relevant positions, the structures of different conformers were extracted from the CoDNas database (Monzon et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Proteome-wide analyses have been performed to identify domains enriched in missense mutations [45,47] [50] and to identify domain-centric positions of hotspot missense mutations [48,49] [50]. These studies focused exclusively on missense mutation and as yet, little attempt was to use these data to distinguish between activating and loss of function mutations in the majority of cases.…”
Section: Domain-based Approaches At Identifying Mutational Hotspotsmentioning
confidence: 99%
“…3A, 3B) confirmed that both cystatin SN protein species (27 and 34) were not phosphorylated. At least three polymorphisms involving a variation in pI have been reported for cystatin SN: N 129 -N D, R 131 -N M, K 135 -N N [42]. By analyzing the MS/MS spectra of the tryptic peptides obtained from spots 27 and 34, it was possible to exclude the presence of the substitution at position 129, but not the substitutions at position 131 and 135.…”
Section: Other Secreted Proteinsmentioning
confidence: 99%